Islamic Values in Lecturer Competency Development: A Systematic Literature Review of Trends, Frameworks, and Impacts in Islamic Higher Education - Orgianus, Yan; Oemar, Hirawati; Praseytaningsih, Endang; Khairo Amalia, Hani (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2024)
Purpose – This study examines the integration of Islamic values into lecturer competencies in Islamic higher education, addressing how principles such as sidq (honesty), amanah (trustworthiness), and al-mas’ūliyyah (responsibility) enhance professional teaching practices and educational outcomes. It aims to propose a value-based competency framework for holistic lecturer development. Design/methods/approach – A systematic literature review (SLR) was conducted on 16 peer-reviewed studies published between 2016 and 2023, retrieved from the Scopus database using key terms